2022
DOI: 10.3389/fendo.2022.893164
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Gut Microbiome and Metabolite Profiles Associated With Anabatic Lipid Dysmetabolism in Thyroid Cancer

Abstract: BackgroundCurrently, the high morbidity of individuals with thyroid cancer (TC) is an increasing health care burden worldwide. The aim of our study was to investigate the relationship among the gut microbiota community, metabolites, and the development of differentiated thyroid cancer.Methods16S rRNA gene sequencing and an integrated LC–MS-based metabolomics approach were performed to obtain the components and characteristics of fecal microbiota and metabolites from 50 patients with TC and 58 healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
(51 reference statements)
2
15
0
Order By: Relevance
“…The intestinal flora is a key factor involving lipid metabolism and obesity [ 41 ], and changes in its components are related to aberrant inflammation and metabolisms like inflammation-related bowel illness, irritable bowel syndrome, and corpulency [ 42 ]. In recent years, it has become a new hotspot to analyze diseases by establishing an internetwork model of microbiota and metabolites [ 43 ]. In our study, the 16S rDNA analysis showed that the high-fat diet and JPTGY evidently affected the composition architectures of the intestinal flora in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal flora is a key factor involving lipid metabolism and obesity [ 41 ], and changes in its components are related to aberrant inflammation and metabolisms like inflammation-related bowel illness, irritable bowel syndrome, and corpulency [ 42 ]. In recent years, it has become a new hotspot to analyze diseases by establishing an internetwork model of microbiota and metabolites [ 43 ]. In our study, the 16S rDNA analysis showed that the high-fat diet and JPTGY evidently affected the composition architectures of the intestinal flora in mice.…”
Section: Discussionmentioning
confidence: 99%
“…After exclusion in title & abstract screening, ten studies remained for full text screening and finally, we included 4 studies with available LDA score of gut microbiota abundance in thyroid cancer patients compared with healthy participants. (11)(12)(13)(14) There were minimal discrepancies between authors in the duplication of the search strategy. (12,14) and 3.5 for Yu et al (11) We searched microbiota with significant MR results in the observational studies and compared MR effect size with significant LDA score reported.…”
Section: Systematic Review and Comparison With Observational Studiesmentioning
confidence: 99%
“…(11)(12)(13)(14) There were minimal discrepancies between authors in the duplication of the search strategy. (12,14) and 3.5 for Yu et al (11) We searched microbiota with significant MR results in the observational studies and compared MR effect size with significant LDA score reported. Among the 11 taxa with significant MR results, 4 were reported with significant LDA scores in observational studies, including Proteobacteria phylum, Streptococcaceae family, Ruminococcus2 genus, and Holdemanella genus (Figure 6).…”
Section: Systematic Review and Comparison With Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that miRNA expression is regulated by the gut microbiota, which in turn affects the host transcriptome and thus the development of CRC [ 49 ]. Lu et al [ 50 ] experimentally established that 27 hydroxycholesterol (27HC), cholesterol and other metabolites, as well as bacteria closely related to lipid metabolism, were significantly reduced in the thyroid cancer group. Among them, 27HC was significantly related to metabolism-related microorganisms ( g_Christenenellaceae_R-7_group ).…”
Section: The Relationship Between the Gut Microbiota And Cancermentioning
confidence: 99%